1955
DOI: 10.1161/01.cir.11.5.789
|View full text |Cite
|
Sign up to set email alerts
|

Dye Dilution Curves and Cardiac Output in Newborn Infants

Abstract: The pattern of ldye dilution curves and the cardiac output was studied in 29

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1956
1956
1982
1982

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…They deduced that there was in these infants a right-left shunt, probably through a patent ductus arteriosus. Prec & Cassels (1955) found that a large proportion of infants less than 15 hr old showed abnormal dye dilution curves after injection of T-1824 into the umbilical vein. These were attributed to persistent patency of the ductus arteriosus.…”
Section: Discussionmentioning
confidence: 98%
“…They deduced that there was in these infants a right-left shunt, probably through a patent ductus arteriosus. Prec & Cassels (1955) found that a large proportion of infants less than 15 hr old showed abnormal dye dilution curves after injection of T-1824 into the umbilical vein. These were attributed to persistent patency of the ductus arteriosus.…”
Section: Discussionmentioning
confidence: 98%
“…Values for cardiac index in newborn infants range from 2.5 to 4.0 liters/min/m 2 [11,26]; in the adult the average value for cardiac index is 3.12 liters/min/m 2 [7]. Mean systemic arterial pressure increases from approximately 60 to 70 mm Hg [20,34] in the immediate newborn period, to 100 mm Hg at puberty [12].…”
Section: Age-related Changes In Rbf In Human Infantsmentioning
confidence: 99%
“…This is mainly becauise only those metho(ds wlhichi require no active cooperationi on the part of' the suibject can be applied to inf:aints. Moreover, there is an additional problem in obtaining reliable data dturing the early neonatal period, since there is conisiderable evidence to stuggest that many healthfy newborni infants, especially those born premncatuirely, continue to have some left to right slhuint dturing at least the 1st wk of life (8)(9)(10)(11). This wouild restult in rapid recirctulation, distturbing the uiptake of soluble inert gases and thereby cauising Qc eff' to be tunderestimiiated.…”
Section: Introductionmentioning
confidence: 99%